PALINOLOGÍA ESTRATIGRÁFICA DEL JURÁSICO DE LA SIERRA DE CHACAI CO Y ADYACENCIAS (CUENCA NEUQUINA, REPÚBLICA ARGENTINA). I. ESTRATIGRAFÍA DE LAS FORMACIONES SIERRA CHACAI CO, LOS MOLLES, CURA NIYEU Y LAJAS (Ameghiniana, 2013)
Stratigraphic sections of Lower and Middle Jurassic formations of Sierra de Chacal Co (Neuquén Province) are described. The Sierra Chacal Co Formation, with Radstockiceras behrendseni, is Pliensbachian in age. The formational name Los Molles is used in the restricted sense of Weaver ( 1931); it ranges from the Toarcian to the Aalenian. The fossiliferous marls, siltstones and calcarenites of the Cura Niyeu Formation are Bajocian in age and are covered by the deltaic sandstones of the Lajas Formation ( Lower Callovian) , followed by the here continental Loteoa Formation (Middle Callovian). Stratigraphic position of guide-ammonoids and of microfloras -gauged by ammoooids- are given. Description of the microfloras will follow in parts II (Sierra Chacai Co and Los Molles formations ) and III (Cura Niyeu and Lajas formations ).